Entrepreneur to millionaire : how to build a highly profitable, fast-growth company and become embarrassingly rich doing it - Billingsley, Kent (McGraw-Hill Education, 2021)
"From the entrepreneurial business transformation expert known as America's Revenue Growth® Architect comes a proven explosive growth road map that has driven more than $1 billion in sales and revenue for small companies and tens of billions of dollars for corporations. If you are among the 27 million U.S. entrepreneurs, Entrepreneur to Millionaire was written for you. The book reveals Kent Billingsley's proven formula for transforming good businesses into fast growth, highly profitable companies. This methodology is repeatable, predictable, and scalable-and guaranteed to improve results in any type and size business, if faithfully applied. For nearly three decades, Billingsley has been turning entrepreneurs, who are hungry for success, into millionaires using his framework, often, without spending additional dollars on marketing or hiring more salespeople. His business-changing, four-phase approach-Revenue Ready, Market Ready, Go to Market, and Own the Market-has been rigorously tested in startups and billion-dollar firms alike. Are you ready to get embarrassingly rich?"--